Selected Topics on Information Systems Engineering: Editorial Introduction to Issue 9 of CSIMQ - Sergio Espana; Mirjana Ivanovic (Complex Systems Informatics and Modeling Quarterly)
This issue of the journal of Complex Systems Informatics and Modeling (CSIMQ) presents papers that discuss selected topics on information systems engineering. The papers are extended versions of selected papers from the CAiSE Forum 2016 held in Ljubljana, Slovenia. The CAiSE Forum is a place within the International Conference on Advanced Information Systems Engineering for disseminating and debating new ideas and tools related to this area.